1975
DOI: 10.1007/bf01905620
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the size of acute, experimental myocardial infarction by Verapamil

Abstract: The effect of 0.1 mg/kg Verapamil on the extent of the ischemic area following ligation of a branch of the left descending coronary artery was studied in anesthetized open chest dogs. The sum of the ST-segment elevation during the entire period of occlusion in the epicardial ECG was 15 mV in control infarction compared to 9 mV (p smaller than 0.0005) when Verapamil was infused after ligation. Mean flow in the left descending coronary artery was reduced by coronary ligation alone on the average by 23%, but augm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1980
1980
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Reduction of calcium flux reduces myocardial contractility and hence myocardial oxygen consumption. It can also result in systemic vasodilation with afterload reduction and vasodilation of coronary collateral vessels supplying the ischemic zone (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of calcium flux reduces myocardial contractility and hence myocardial oxygen consumption. It can also result in systemic vasodilation with afterload reduction and vasodilation of coronary collateral vessels supplying the ischemic zone (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that verapamil and cardioplegia do not directly inhibit calcium entry on reperfusion is in contrast to many studies (Wende et al, 1975;Reimer et al, 1977;Smith et al, 1977;Lefer et al, 1979) which have shown that, when given prior to a period of ischemia, calcium antagonists delay or prevent tissue damage, and also reduce calcium accumulation Witts et al, 1979;Lefer et al, 1979;Nayler et al, 1980). There are fewer reports of the effects of calcium antagonists given after the onset of ischemia.…”
Section: Camentioning
confidence: 94%
“…Verapamil and other calcium antagonists block the slow calcium current of the action potential (Kohlhardt et al, 1972a(Kohlhardt et al, , 1972bCranefield et al, 1974;Kohlhardt and Mnich, 1978;Henry, 1980). When these drugs are given prior to or at the onset of a period of ischemia, they have been shown to preserve tissue ultrastructure (Reimer et al, 1977), to reduce enzyme release (Wende et al, 1975;Smith et al, 1977;Lefer et al, 1979), to diminish S-T elevation (Lefer et al, 1979;Selwyn et al, 1979), to improve hemodynamic function (Magee et al, 1979;Clark et al, 1979), to maintain tissue ATP (Lefer et al, 1979;Watts et al, 1979;Nayler et al, 1980;Weishaar and Bing, 1980), and to prevent calcium accumulation in whole tissue and isolated mitochondria Watts et al, 1979;Lefer et al, 1979;Nayler et al, 1980). The uniformly beneficial results obtained in such experiments are in sharp contrast to the results of experiments in which calcium antagonists have been administered, not prior to ischemia, but either after the ischemic myocardium has ceased to contract or at the time of reperfusion.…”
mentioning
confidence: 99%
“…As a consequence, the early conceptual approaches to infarct limitation in the 1970s centered on agents to reduce myocardial oxygen demand or vasodilators to increase oxygen and metabolic substrate delivery (Maroko et al, 1971;Braunwald and Maroko, 1975). Hence, agents such as ␤-adrenoceptor antagonists Reynolds et al, 1981;Downey et al, 1982); calcium channel blockers (Reimer and Jennings, 1984;Reimer et al, 1985;Wende et al, 1975); and glyceryl trinitrate (Bleifeld et al, 1973;Malm et al, 1979;Fukuyama et al, 1980) were extensively investigated with no consistently reproducible evidence of infarct limitation.…”
Section: B Experimental Approaches To Infarct Size Limitationmentioning
confidence: 99%